3D point cloud from Nakadake Sanroku Kiln Site Center, Japan: sample data for the application of adaptive filtering with the AFwizard - Shinoto, Maria; Doneus, Michael; Haijima, Hideyuki; Weiser, Hannah; Zahs, Vivien; Kempf, Dominic; Daskalakis, Gwydion; Höfle, Bernhard; Nakamura, Naoko (Universität, 2022)
This data set represents 3D point clouds acquired with LiDAR technology and related files from a subregion of 150*436 sqm in the ancient Nakadake S...